La portada de la Década Primera de la historia de la insigne, y coronada ciudad y Reyno de Valencia (1610): compendio iconográfico de la historia valenciana - Chiva Beltrán, Juan (Millars. Espai i Història, 2010)
The historiographical volume Década Primera (1610), written by Gaspar Juan Escolano, shows an interesting architectural cover, in the tradition of the Hispanic Baroque, which explaines the history of the Valencian Kingdom through the portraits of its leading figures.